Views of a good life and allostatic load: Physiological correlates of theories of a good life depend on the socioeconomic context. Issue 5 (2nd September 2016) - Levine, Cynthia S.; Atkins, Alexandra Halleen; Waldfogel, Hannah Benner; Chen, Edith
Abstract: This research examines the relationship between one's theory of a good life and allostatic load, a marker of cumulative biological risk, and how this relationship differs by socioeconomic status. Among adults with a bachelor's degree or higher, those who saw individual characteristics (e.g. personal happiness, effort) as part of a good life had lower levels of allostatic load than those who did not. In contrast, among adults with less than a bachelor's degree, those who saw supportive relationships as part of a good life had lower levels of allostatic load than those who did not. These findings extend past research on socioeconomic differences in the emphasis on individual or relational factors and suggest that one's theory of a good life has health implications.